2021
DOI: 10.3389/fmicb.2021.705758
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lactobacillus plantarum P8 on Growth Performance, Intestinal Health, and Microbiota in Eimeria-Infected Broilers

Abstract: Coccidiosis is one of the major parasitic diseases in the commercial broiler industry. Probiotics can protect poultry against Eimeria infection. However, the mechanisms are not fully known. Therefore, Lactobacillus plantarum P8 (P8) was used to investigate its anti-coccidial property and mechanism. Five hundred broilers were allocated to five treatments: control diet (NC), control diet + Eimeria infection (IC), control diet containing 1 × 107 cfu/g P8 + Eimeria infection (P8L), control diet containing 1 × 108 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 59 publications
(67 reference statements)
0
34
0
Order By: Relevance
“…In a study 35 , drinking of acetic acid resulted in protective effects against E. tenella probably by decreasing pH of ceca, obliteration of oocysts, and protection of the epithelium and finally decrease of BD in chickens. However, diclazuril were effective in reducing oocyst shedding 6 . The reduced bleeding can protect infected birds against secondary infections, inflammatory response, and toxic substances absorption 42 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In a study 35 , drinking of acetic acid resulted in protective effects against E. tenella probably by decreasing pH of ceca, obliteration of oocysts, and protection of the epithelium and finally decrease of BD in chickens. However, diclazuril were effective in reducing oocyst shedding 6 . The reduced bleeding can protect infected birds against secondary infections, inflammatory response, and toxic substances absorption 42 .…”
Section: Discussionmentioning
confidence: 90%
“…Wang et al . (2021) reported that dietary supplementation of Lactobacillus plantarum or diclazuril decreased the oocysts shedding 6 . In a study 35 , drinking acetic acid resulted in protective effects against E. tenella probably by declining pH of ceca and obliteration of oocysts in chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, diclazuril is the most common chemistry medicine in the coccidial infection, which can be used to reverse the microbial changes induced by Eimeria spp. (Wang et al, 2021). However, some research treatment of enrofloxacin and diclazuril altered the abundance of gut microbiota and their functional metabolite pathways, reducing bacterial diversity while expanding and collapsing composition of specific indigenous microbes, than formed a new microbial community (Elokil et al, 2020).…”
Section: The Anti-coccidial Application Of Probioticsmentioning
confidence: 99%
“…Many Limosilactobacillus species have “Qualified Presumption of Safety (QPS)” status from the European Food Safety Authority (EFSA) and “Generally Regarded As Safe (GRAS)” status from US Food and Drug Administration (FDA). Lactobacilli are key members of the endogenous microbiota of oral, GI, respiratory, and urogenital mucosa and play a key role in regulating local microbiota, restoring barrier function, preventing inflammation associated with GI diseases, improving growth performance, and protecting against infectious diseases (Chen et al, 2021 ; Han et al, 2021 ; Hu et al, 2021 ; Klaenhammer et al, 2002 ; Li et al, 2018 ; Manes‐Lazaro et al, 2017 ; Ouwehand et al, 2002 ; Siddique et al, 2021 ; Vineetha et al, 2017 ; Y. Wang et al, 2021 ; Wu et al, 2021 ). Of particular importance, Lactobacilli have been shown to possess strong antagonistic activity against C. perfringens , inhibit toxin production, reduce proinflammatory cytokines, improve intestinal integrity and immune response, correct microbial dysbiosis, restore performance deficiencies associated with subclinical NE, and protect chickens from clinical NE (Dec et al, 2016 ; Gong et al, 2020 ; Guo et al, 2017 , 2021 ; Khalique et al, 2019 ; Kizerwetter‐Swida & Binek, 2005 , 2009 , 2016 ; La Cao et al, 2012 ; La Ragione et al, 2004 ; Li et al, 2017 ; Shojadoost et al, 2022 ; Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%